Advisor understanding of their roles in the advisory system: a comparison of governance structures in Argentina, Australia, Brazil, and New Zealand - Turner, James A. (2023)
Purpose: Explore advisor understanding of their roles in advisory systems characterised by differing mixes of public and private funding and delivery. Methodology: A systems perspective of advisory system governance is combined with an individual perspective of advisor roles. Data from a survey of 38 Australian, 19 New Zealand, 606 Argentine and 279 Brazilian respondents were analysed for statistical differences. Findings: In all contexts, advisor priorities reflect state or industry goals. Where there is more private funding and delivery, advisors also prioritise farmer commercial goals. Under public extension funding and delivery, group methods and capacity building are emphasised to reach many farmers and realise public goals. Practical implications: Advisors play a crucial role in reconciling competing national, industry and farmer goals at the farm-level. This emphasises participatory methods and intermediary positions in the advisory system to facilitate dialogue and support farmers to realise competing goals. A policy implication is public and industry funding is needed for advisors to engage with public and industry organisations to understand and contribute to policies and objectives they will be advising on. Theoretical implications: Combining a systems perspective of country-level advisory system governance with an individual perspective of advisor roles highlights that advisor understanding of their roles are related to the public governance context in which they operate. Originality/value: The advisor understanding of their roles in the advisory system is related to different governance of pluralistic advisory systems. This contributes to articulating advisory policies and practices to support coordination and inclusion in pluralistic advisory systems.